ANALISIS KADAR AIR (MOIST) DAN KADAR KOTORAN (DIRT) INTI SAWIT PADA KERNEL STORAGE BIN (KSB) - Elsa Shalsabilla; Miftahul Husnah (Universitas Islam Sumatera Utara, 2025)
The quality of palm kernels is an important factor in determining the quality of palm kernel oil (PKO). The main parameters used in kernel quality control are moisture content and dirt content. This study aims to analyze the moisture and dirt content of kernels that have undergone the drying process in the kernel silo and compare them with the company's quality standards. The method used is laboratory analysis with a gravimetric approach for moisture content and a physical separation method for dirt content. The test results show that the moisture content ranges from 5.11% to 6.22% and the dirt content ranges from 5.65% to 5.94%. These values are still within the company's quality standards, which are 6.00–7.00% for moisture content and 5.00–6.00% for dirt content. This indicates that the kernel processing and storage process is still running well.